Representation of the Houthis After the Hamas-Israel Ceasefire in Arab Online Media: A Critical Discourse Analysis Perspective - Wahid, Muhammad Aqil; Fitriani, Laily; Al Anshory, Abdul Muntaqim (Study Program of Arabic Language Teaching, 2026)
This study examines the representation of the Houthi movement in Arab online media following the Hamas–Israel ceasefire, focusing on how linguistic choices construct political meaning and ideological positioning. Employing a qualitative descriptive design, the research applies Norman Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA), which includes textual analysis, discursive practice, and socio-cultural practice. The primary data consist of online news texts from various Arab media outlets including Belqees.net, Asharq Al-Awsat, Al-Ain Al-Ikhbariyah, Erem News, Al-Mashhad News, YeniYemen, and News Yemen, collected through reading and note-taking techniques, and analyzed using Fairclough’s CDA framework. The findings reveal that the analyzed Arabic online media outlets construct the Houthis through a predominantly negative discursive framework characterized by delegitimization, criminalization, and externalization. At the textual level, this is achieved through evaluative lexical choices, derogatory labels, and grammatical constructions that portray the Houthis as an illegitimate militia, a proxy of Iran, and a source of regional instability. At the level of discursive practice, these representations are reproduced through intertextual reporting patterns, selective sourcing, and the circulation of expert opinions that reinforce anti-Houthi narratives. At the socio-cultural level, the discourse reflects broader geopolitical and ideological contestations between Iranian-aligned actors and Gulf regional powers. The findings therefore demonstrate how media discourse functions as a form of symbolic power that contributes to the construction and legitimization of particular political interpretations of the Houthis and their role in regional conflicts.